Arduino based digital IC tester: article / Mohd Adib Sulaiman - Sulaiman, Mohd Adib (2013)
Nowadays integrated circuits (IC) chip is rapidly growth and become more complexity. The need of devices that can test this IC chip reliable and low cost is very necessary. This paper describes a low cost digital IC tester implemented using the Arduino Mega 2560 microcontroller. The digital IC tester receives keypad information about the chip under test, then the microcontroller will send digital signal to the chip. The resulting chip outputs are then compare with the IC chip expected result to determine whether chip under test is faulty or not.